The Loney - Hurley, Andrew Michael, 1975- (Boston : Houghton Mifflin Harcourt, 2016)
"The eerie, suspenseful debut novel -- hailed as "an amazing piece of fiction" by Stephen King -- that is taking the world by storm. When the remains of a young child are discovered during a winter storm on a stretch of the bleak Lancashire coastline known as the Loney, a man named Smith is forced to confront the terrifying and mysterious events that occurred forty years earlier when he visited the place as a boy. At that time, his devoutly Catholic mother was determined to find healing for Hanny, his disabled older brother. And so the family, along with members of their parish, embarked on an Easter pilgrimage to an ancient shrine. But not all of the locals were pleased to see visitors in the area. And when the two brothers found their lives entangling with a glamorous couple staying at a nearby house, they became involved in more troubling rites. Smith feels he is the only one to know the truth, and he must bear the burden of his knowledge, no matter what the cost. Proclaimed a "modern classic" by the Sunday Telegraph (UK), The Loney marks the arrival of an important new voice in fiction."--
Keywords: Catholic Church -- England -- Fiction; Rites and ceremonies -- England -- Fiction; Interpersonal relations -- Fiction; Suspense fiction; Psychological fiction